Extended Thrombolysis In Cerebral Infarction (eTICI) grade 2c: a potential angiographic target for endovascular treatment in acute basilar artery occlusion?. (15th November 2021) - Chen, Luming; Zhao, Chenghao; Song, Jiaxing; Zi, Wenjie; Sang, Hongfei; Yuan, Junjie; Huang, Jiacheng; Li, Linyu; Luo, Weidong; Fu, Xinmin; Zhou, Peiyang; Wan, Yue; et al.
Abstract : Background: Higher extended Thrombolysis In Cerebral Infarction (eTICI) grades are associated with better clinical outcomes after endovascular treatment (EVT) for proximal intracranial occlusion of the anterior circulation. However, the relationship between eTICI grade and outcomes after EVT in patients with acute basilar artery occlusion (BAO) remains unclear. We aimed to explore which eTICI category was the cut-off correlating with better clinical outcomes in patients with BAO undergoing EVT. Methods: We included patients treated via EVT from the BASILAR study. Multivariable logistic regression analyses were performed to assess the impact of eTICI grades on 90-day favorable functional outcomes, defined as a modified Rankin Scale (mRS) score of 0–3. Other outcomes were functional independence (mRS 0–2), all-cause mortality, and symptomatic intracranial hemorrhage. Results: Among 647 patients treated with EVT, 127 (19.6%), 128 (24.5%), 110 (21.1%), and 282 (54%) patients achieved eTICI grades of 0–2a, 2b, 2c, and 3, respectively. Compared with eTICI grades 0–2a, higher rates of favorable functional outcomes (adjusted OR (aOR) 2.96, 95% CI 1.33 to 6.57, and aOR 7.40, 95% CI 3.63 to 15.09, respectively) were observed for grades 2c and 3, not 2b (aOR 1.93, 95% CI 0.86 to 4.36). The risks of mortality and symptomatic intracranial hemorrhage were also lower for eTICI grades 2c and 3 than for grades 0–2a. Conclusions: An eTICI grade of 2c/3 may be a target for successful reperfusion after EVT in patients with acute BAO; however, further studies with larger sample sizes and clinical trials are needed.